Demand for abortion and post abortion care in Ibadan, Nigeria - Bosede O. Awoyemi; Jacob Novignon (Health Economics Review, 2014)
Background: While induced abortion is considered to be illegal and socially unacceptable in Nigeria, it is still practiced by many women in the country. Poor family planning and unsafe abortion practices have daunting effects on maternal health. For instance, Nigeria is on the verge of not meeting the Millennium development goals on maternal health due to high maternal mortality ratio, estimated to be about 630 maternal deaths per 100,000 live births. Recent evidences have shown that a major factor in this trend is the high incidence of abortion in the country. The objective of this paper is, therefore, to investigate the factors determining the demand for abortion and post-abortion care in Ibadan city of Nigeria. Methods: The study employed data from a hospital-based/exploratory survey carried out between March to September 2010. Closed ended questionnaires were administered to a sample of 384 women of reproductive age from three hospitals within the Ibadan metropolis in South West Nigeria. However, only 308 valid responses were received and analysed. A probit model was fitted to determine the socioeconomic factors that influence demand for abortion and post-abortion care. Results: The results showed that 62% of respondents demanded for abortion while 52.3% of those that demanded for abortion received post-abortion care. The findings again showed that income was a significant determinant of abortion and post-abortion care demand. Women with higher income were more likely to demand abortion and post-abortion care. Married women were found to be less likely to demand for abortion and post-abortion care. Older women were significantly less likely to demand for abortion and post-abortion care. Mothers' education was only statistically significant in determining abortion demand but not post-abortion care demand. Conclusion: The findings suggest that while abortion is illegal in Nigeria, some women in the Ibadan city do abort unwanted pregnancies. The consequence of this in the absence of proper post-abortion care is daunting. There is the need for policymakers to intensify public education against indiscriminate abortion and to reduce unwanted pregnancies. In effect, there is need for effective alternative family planning methods. This is likely to reduce the demand for abortion. Further, with income found as a major constraint, post abortion services should be made accessible to both the rich and poor alike so as to prevent unnecessary maternal deaths as a result of abortion related complications.
Keywords: 330; Abortion; Post abortion care; Nigeria; Probit